Nominative practices in the far south of Portuguese America: Nossa Senhora da Madre de Deus de Porto Alegre parish (1772-1839): Nominative practices in the far south of Portuguese America: Nossa Senhora da Madre de Deus de Porto Alegre parish (1772-1839) (Revista de História da UEG (REVHIST), 2024)
From the systematic collection of information contained in baptismal records of the Mother of God Parish, in Porto Alegre (RS), from 1772 to 1839, the most popular given names attributed to newborns, whether free, freed, or enslaved, were identified. According to theoretical foundation, the results obtained during the research proved to be similar to those of other regions of Portuguese America within the aforementioned chronological scope. In this perspective, if names were chosen merely by chance, the persistent repetition of certain given names over time would be implausible. The attribution of names to offspring involves issues of socialization, tradition, power, and devotion. The favoritism of specific given names, linked to religiosity, indicates the existence of a cultural identity rooted in Catholicism.Keywords: Naming practices. Cultural identity. Religiosity. Portuguese America. Catholicism.